Respuesta :

Answer:

369

Step-by-step explanation:

g(f(x)) simply means to put the whole expression of function f(x) into the place of "x" in g(x).

and to find the functional value for a specific x we just need to calculate functional value for f(x) and use that result as input for g(x).

f(6) = 8×6 + 5 = 48 + 5 = 53

and now

g(53) = 7×53 - 2 = 371 - 2 = 369

to check we do the general functional substitution :

g(f(x)) = 7×(8x+5) - 2 = 56x + 35 - 2 = 56x + 33

g(f(6)) = 56×6 + 33 = 336 + 33 = 369

correct